Social Media and Purchase Habits of Consumers - Parajuli, Suman Kamal; Budhathoki, Dhruba Kumar (Management Dynamics, 2022)
This research focused on social media’s impact on purchasing decisions in the Lalitpur district. Through the convenience sample, two-hundred responses were obtained through five-point Likert-type questionnaires. Based on descriptive statistics, correlation analysis, and regression analysis, Consumers’ actions were shown to be significantly and positively correlated with the degree to which they trusted content shared on social media platforms. However, perceived risk was found to have a negative and significant relationship with consumer behavior. In addition, the perceived value was found to have a significant positive association with consumer behavior. The regression analysis showed that trust in social media and perceived value significantly affect consumer behavior. At the same time, perceived risk was found to have a significant adverse effect on consumer behavior. This study concluded that the impact of social media has a significant effect on consumer behavior in Lalitpur District.